Adult immunization against hepatitis B: Does the number of jabs matter?. Issue 26 (9th June 2022) - Oster, Gerry; Bornheimer, Rebecca; Ottino, Kevin; Stevenson, Catherine; Lewin, Clem; Janssen, Robert
Highlights: Adult HBV immunization. Adherence with multi-dose vaccines. Cost per person seroprotected. Three-dose vs two-dose HBV vaccines. Abstract: Background: At least one-half of adults beginning an immunization series with a three-dose hepatitis B virus (HBV) vaccine (ENGERIX-B, RECOMBIVAX-B) have been reported not to receive the third dose. Use of a two-dose vaccine may improve adherence and lead to greater overall levels of seroprotection. Objective: To examine expected levels of adherence and overall seroprotection at one year among adults in routine clinical settings beginning an immunization series with either ENGERIX-B or the two-dose HBV vaccine, HEPLISAV-B. Methods: Decision-analytic model comparing expected levels of adherence and overall seroprotection at one year among a hypothetical cohort of one million previously unvaccinated adults aged ≥ 30 years receiving first doses of either ENGERIX-B or HEPLISAV-B in a routine clinical setting. We stratified the population by age (30–49 years vs ≥ 50 years) to allow for possible differences in adherence and seroprotection. We estimated our model using published adherence rates for HBV vaccines, and reported seroprotection rates by number of doses administered. We also compared total expected costs of HBV immunization with each vaccine. Results: Use of a two-dose rather than three-dose HBV vaccine would increase the expected number of adults seroprotected at one year by 275, 000 per one million persons beginning immunization series, largely reflecting a gain of 290, 000 in the expected number of persons fully vaccinated. Results were similar for the two age groups. While the cost per dose of HEPLISAV-B exceeds that of ENGERIX-B, its estimated mean cost per person seroprotected at one year is $50-$70 (∼15%) lower. Conclusions: Use of a two-dose HBV vaccine would increase the number of adults fully seroprotected at one year compared with the number expected with a three-dose vaccine. Notwithstanding its higher unit cost, mean expected cost per person seroprotected is substantially lower for HEPLISAV-B than ENGERIX-B as a result of much higher levels of seroprotection.